De Quervain’s Tenosynovitis Virally Exacerbated by SARS-CoV-2 and Influenza Infections: A Case Report - Maria Gergoudis; Logan Laubach; Glenn E. Lee; Jeffrey R. Donowitz (Case Reports in Infectious Diseases)
We present the case of a fully vaccinated 39-year-old male with no pertinent past medical history who initially presented with De Quervain’s tenosynovitis which was successfully treated with a corticosteroid injection. His symptoms recurred during a COVID-19 infection, which was treated with a repeat corticosteroid injection. Symptoms recurred during an influenza infection and were subsequently treated with a first dorsal compartment release. The etiology of De Quervain’s tenosynovitis remains unclear. It has classically been categorized as a noninflammatory degenerative process, but recent evidence suggests a possible inflammatory connection. Here, we present a case of recurrent De Quervain’s tenosynovitis exacerbated by two distinct viral infections. We hypothesize that viral-induced systemic inflammation led to localized recurrence of inflammation within the tendon sheath. Further studies including cytokine analysis and inflammatory markers are needed to advance this hypothesis.